Computational mechanics, materials and engineering applications : selected, peer reviewed papers from the 2011 International Workshop on Computational Mechanics, Materials and Engineering Applications (CMMEA 2011), July 23-24, 2011, Kunming, China - Yang, Jianrong; Yu, Min (Applied mechanics and materials, 2012)
Following the great progress made in Computational Mechanics and Materials, the 2011 International Workshop on Computational Mechanics, Materials and Engineering Applications (CMMEA 2011) aimed at providing a forum for the presentation and discussion of state-of-the-art developments in Computational Mechanics and Engineering Applications, Building Materials, Geotechnical & Soil Engineering and Materials Science and Engineering Applications. The emphasis was placed on basic methodologies, scientific developments and engineering applications. Review from Book News Inc.: This publication consists.